2017
DOI: 10.1111/and.12744
|View full text |Cite
|
Sign up to set email alerts
|

Metabonomic analysis of fatty acids in seminal plasma between healthy and asthenozoospermic men based on gas chromatography mass spectrometry

Abstract: The mechanism of asthenozoospermia remains unclear. The knowledge of the metabolism of fatty acids in seminal plasma is important and meaningful for the pathological study of asthenozoospermia. We present an optimised assay of extraction and derivatisation followed by GC/MS to analyse metabolites, especially fatty acids, in seminal plasma from healthy and asthenozoospermic men. Eighty-nine peaks including 17 kinds of fatty acids were analysed and identified in the chromatogram. The GC/MS data were analysed usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 26 publications
5
24
0
Order By: Relevance
“…As in bull seminal plasma, citric acid is also found in semen of other species, such as boar [ 62 ], human [ 26 , 59 ], and rabbit [ 63 ]. Citric acid helps control pH in boar semen and acts as a chelator for zinc, magnesium, and calcium [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…As in bull seminal plasma, citric acid is also found in semen of other species, such as boar [ 62 ], human [ 26 , 59 ], and rabbit [ 63 ]. Citric acid helps control pH in boar semen and acts as a chelator for zinc, magnesium, and calcium [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…Both urea and phosphoric acid were detected in the seminal plasma samples of our study. Urea has also been found in human seminal fluid [ 20 , 26 , 67 ], however, the main role it plays in semen is still unknown. Given that urea is an end product of protein metabolism [ 68 ] and that seminal fluid contains protein, it is possible that seminal plasma urea is the consequence of protein degradation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In recent years, studies using approaches in metabolomics have revealed potential fertility biomarkers in the seminal plasma of humans [27, 28], stallions [12], and bulls [29]. In a recent publication, we reported the identification of 63 compounds in bull seminal plasma by using gas chromatography-mass spectroscopy (GC-MS).…”
Section: Introductionmentioning
confidence: 99%